PENGARUH DIVERSIFIKASI GENDER GENERASI Z TERHADAP PERILAKU KEPUTUSAN INVESTASI - Astia Putriana; Gati Anjaswari; M.Riduan Abdillah (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2023)
This research aims to find empirical evidence of the effect of gender diversification on investment decision behavior. This research method is quantitative. The research population was D3 students of the accounting study program class of 2020 at the Tanah Laut State Polytechnic as a State University (PTN) and undergraduate students of the accounting study program class of 2019 and 2020 at the Banjarmasin National STIE as a Private University (PTS). The research sampling technique used purposive sampling method. The exogenous variable is gender diversification as measured using a dummy while the endogenous variable is investment decision behavior as measured through a questionnaire. The results of this research found empirically that gender diversification has a significant effect on Investment Decision Behavior as indicated by the magnitude of p <0.001 with the R Square value still relatively low, namely only 7%, meaning that the influence of other factors is still a lot to influence investment decision behavior apart from diversification gender. Keywords : Z Generation, Gender Diversification, Behavior, Investment Decision